2020
DOI: 10.1177/1050651920958503
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Expertise During the Pandemic

Abstract: This article addresses how social media platforms can better highlight expert voices through design choices. Misinformation, after all, has exploded during the Covid-19 pandemic, and platforms have struggled to address the issue. The authors examine this critical gap in validation mechanisms in the current social media platforms and suggest possible solutions for this urgent problem with third-party partnerships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Existing studies on senior tourism have usually relied on information from tourists and individuals. However, during a crisis such as the pandemic, it is important to take expert opinions into account (Baniya and Potts, 2021). This study offers a model based on expert opinions that predicts the destination choice intentions of senior tourists.…”
Section: Proposed Model For Senior Tourismmentioning
confidence: 99%
“…Existing studies on senior tourism have usually relied on information from tourists and individuals. However, during a crisis such as the pandemic, it is important to take expert opinions into account (Baniya and Potts, 2021). This study offers a model based on expert opinions that predicts the destination choice intentions of senior tourists.…”
Section: Proposed Model For Senior Tourismmentioning
confidence: 99%
“…Some studies in the review explored the topic of actionable items that could be imposed on the public to limit the spread of misinformation. One such suggestion was to implement a standard for validating professional status that could be displayed on social media to relay to the public the credibility of the information being presented [ 30 ]. Research has shown that an “accuracy nudge” intervention, which involved participants in assessing the accuracy of the news headline, was an effective way of preventing users on social media from spreading misinformation [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…Other sources demonstrated that public figures with a large following had a significant impact on denouncing misinformation [ 34 ]. Another common consideration of how misinformation was received largely depended on how it was tagged (i.e., as harmful vs. going against public health officials) [ 11 , 28 , 29 , 30 ]. By collectively investigating different components, this scoping review has highlighted potential strategies for limiting the spread of misinformation related to COVID-19 [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…James Fleck notes that while ‘virtually everyone has access to contingent knowledge to some extent, though depending on the structures and relations of power within and between organizations, not everyone’s contingent knowledge is equally recognized, perceived as being relevant, solicited, valued or acted on’ (Fleck, 1998:158), pointing to how the performance and verification of expertise have become far less trusted and more open to manipulation in the contemporary media and communications environment. It is now well established that much contemporary public (particularly political) discourse frames such scholarly or professional displays of expertise as ‘under attack’ or ‘untrustworthy’ (Eyal, 2019) following the treatment of various expert opinions around the climate crisis and, more recently, the Covid-19 pandemic (Baniya and Potts, 2021; Lovari, 2020; van Dijck and Alinejad, 2020).…”
Section: Whose Expertise?mentioning
confidence: 99%